Exploration of Tammate Leaf Potential (Lannea Coromandelica): BSLT Toxicity Test and DPPH Antioxidant Activity (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: The growing use of traditional medicines is accompanied by increased public trust in the effectiveness of herbal remedies. One such plant is Lannea coromandelica L. (Tammate), which is traditionally used for wound healing and lowering blood sugar levels. Scientific validation of its biological activity and safety profile is essential to support its use in pharmaceutical development and ensure its efficacy and safety for wider clinical applications. Objective: This study aimed to assess the bioactivity potential of Tammate leaf ethanol extract by evaluating its in vitro antioxidant activity and toxicity through standardized laboratory procedures. Methods: The extract was prepared through maceration using 96% ethanol as the solvent. Toxicity was tested using the Brine Shrimp Lethality Test (BSLT) on Artemia salina larvae at concentrations of 10, 250, 500, and 750 ppm. Probit analysis was applied to determine LC₅₀ values as indicators of toxicity. Antioxidant activity was measured using the DPPH (1,1-diphenyl-2-picrylhydrazyl) assay to determine IC₅₀ values. Results: The ethanol extract of Tammate leaves showed an LC₅₀ of 415.1 ppm, indicating a toxic effect (since LC₅₀ < 1000 ppm is considered toxic). Its IC₅₀ value was 19.03 ppm, which is relatively close to that of vitamin C as a positive control (2.841 ppm), and therefore categorized as having very strong antioxidant activity. Conclusion: The ethanol extract of Tammate leaves exhibits significant bioactive properties, with strong antioxidant potential and moderate toxicity. These results indicate promising potential for pharmaceutical development, although further research is required to fully assess its safety and therapeutic applicability in humans.